Judicial Corruption: Concept, Actors and Dynamics (Andamios, Revista de Investigación Social, 2025)
How to conceptualize judicial corruption? and which are the actors, dynamics, and exchanges under which this phenomenon operates? are the two research questions this article answers. Based on an interdisciplinary discussion, I define judicial corruption as any act from judges, prosecutors, or officials who, by action or omission, alter the impartial direction or content of a judicial decision in exchange for money, goods, or any other type of benefit. Although the fundamental features of the concept are maintained in any event of judicial corruption, I propose the number of actors, the nature of the interactions and the intensity of the retributions vary depending on the place that the court occupies within the pyramid of the Judiciary Branch.
Keywords: Judicial corruption; judges; non legitim retributions; interactions; prosecutors